2010
DOI: 10.1016/j.jsv.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A computational and experimental study of resonators in three dimensions

Abstract: In a previous work by the present authors, a computational and experimental investigation of the acoustic properties of two-dimensional slit resonators was carried out. The present paper reports the results of a study extending the previous work to three dimensions. This investigation has two basic objectives. The first is to validate the computed results from direct numerical simulations of the flow and acoustic fields of slit resonators in three dimensions by comparing with experimental measurements in a nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…More recently, fully three-dimensional numerical simulations of sound interacting with resonators have been performed with different geometries. Tam et al (2008a) observed the formation of vortex rings in their simulations of a rectangular orifice liner and noted that their earlier results from slit liners had a very different flow topology, a result confirmed by Roche et al (2009). Xu, Li & Guo (2014 extended earlier slit liner simulations into a fully three-dimensional simulation and found the absorption coefficients agreed very well with the previous two-dimensional simulations.…”
Section: Literature Reviewmentioning
confidence: 74%
“…More recently, fully three-dimensional numerical simulations of sound interacting with resonators have been performed with different geometries. Tam et al (2008a) observed the formation of vortex rings in their simulations of a rectangular orifice liner and noted that their earlier results from slit liners had a very different flow topology, a result confirmed by Roche et al (2009). Xu, Li & Guo (2014 extended earlier slit liner simulations into a fully three-dimensional simulation and found the absorption coefficients agreed very well with the previous two-dimensional simulations.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Accurate results were obtained up to a frequency of 2.5 kHz. Tam et al also used DNS in their numerical investigation of resonators in three dimensions [11]. By virtue of its high-fidelity non-modelling approach, DNS is able to reproduce the small scale details of acoustic phenomena (such as dissipation mechanisms) accurately, even for high frequency ranges.…”
mentioning
confidence: 99%
“…In terms of the acoustic performance, numerous holes in the modified design are expected to enhance the acoustic performance of the muffler by acting as slit resonators, which are known to convert acoustic energy into vortical energy by generating vortices (Tam et al, 2005(Tam et al, , 2010). Fig.…”
Section: New Designmentioning
confidence: 99%